FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MEMBELI PIA APEL SHYIF (Studi Kasus: UKM Permata Agro Mandiri Kota Batu, Jawa Timur) - Susi Haryati Mila Sagita (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
ABSTRACTThe purpose of this study is to find out what factors influence consumer decisions in buying pia apel Shyif. This research was conducted at the Brawijaya Souvenir Palace and the Palace of the De Duwa Palace of Batu City, East Java, with the consideration that the souvenir center sells pia apel Shyif products. Sampling using nonprobability sampling technique that is by accidental sampling as many as 70 respondents. The study was conducted in December 2018. Data analysis used descriptive analysis and logit model regression analysis. The results showed that the factors that influence consumer decisions in buying apple pie are price factors, product quality factors, income factors, and gender factors.Keywords: consumer decision,apple pia Shyif